Efficacy of Equal Volume of Ringer Lactate Versus 3.5% Polymer of Degraded Gelatine Solution (Haemaccel) as Preloading Fluid for Prevention of Hypotension after Spinal Anaesthesia for Lower Segment Cesarean Section - Kunwar, BR; Bhattacharyya, P; KC, NB (Medical Journal of Shree Birendra Hospital, 2012)
Introduction: Systemic hypotension is frequently and immediately seen after spinal anaesthesia. Historically Ringer lactate is used to substitute the acute relative volume loss after spinal anesthesia, although it remains in intravenous circulation for a short period. The preloading with 5% albumin and gelatine have become popular and effective as they remain intravascular for a longer duration providing sustained normotension. The aim of this study was to assess the efficacy of equal volume of Ringer lactate and Haemaccel as a preloading fluid for the prevention of hypotension after spinal anaesthesia in patients undergoing Lower Segment Cesarean Section. Methods: This was a prospective comparative study in which Patients were randomly allocated in to Group A and group. Group A patients were preloaded with Ringer lactate 10ml/kg body weight and Group B were preloaded with Haemaccel 10 ml/kg body weight within a period of 5-10 minutes before spinal anaesthesia. After giving the block, blood pressure (systolic, diastolic and mean) were recorded every 2.5 minutes for initial 20 minutes and every 5 minutes during the rest of the period of surgery. Onset of hypotension along with other parameters were recorded and analysed using SPSS ver. 13. Results: All together 100 patients were enrolled in the study, 50 in Group A (Ringer lactate) and 50 in Group B (Haemaccel). The episodses of hypotension was higher in patients who received Ringer lactate as preloading fluid than who received haemaccel as preloading fluid (42% versus 24%). Conclusion: Preloading with Haemaccel gives better hemodynamic stability and lesser incidence of hypotension than that of Ringer lactate. DOI: http://dx.doi.org/10.3126/mjsbh.v10i1.6405 Medical Journal of Shree Birendra Hospital Jan-June 2011 10(1) 1-5